The Relationship between Housing Dampness and Mold and Self-Assessed Health - Benedikt Þorri Sigurjónsson 1983- (2016)
Damp or mold-infested building materials are the hallmark of an unhealthy building. Dampness in itself can contribute to unhealthy indoor air through direct and indirect mechanisms of bacteria, fungi, dust mites and numerous other forms of life that need a humid environment to prosper. As a secondary effect, these organisms can release chemicals that affect humans’ quality of life. Indoor dampness and mold (D&M) is associated with a host of symptoms and conditions leading to overall negative health outcomes for the occupants. This analysis explores the association and potential causal relationship between D&M in homes and adults occupants´ self-assessed health (SAH). A panel dataset (t=4), sampled from the Icelandic population above 16 years, with observations on SAH and D&M in respondents´ dwellings was obtained from Statistics Iceland. Pooled cross-sectional models were specified to investigate the association between D&M and SAH. Additional analysis was conducted using individual fixed effects (FE), with both linear and ordered logit (OL) estimators. To shed some light on the potential causal pathway, health is estimated as a function of lagged D&M, as well as the reverse estimations of D&M as a function of lagged health. Gender differences are also explored. Results indicate a statistically significant association (OR 1.2) between D&M in dwellings and adverse SAH for adults. The FE models show a statistically significant relationship between D&M in dwellings at t-1 and occupants SAH at t, robust to estimation technique and specification. This is in accordance with exposure to D&M leading to adverse SAH and removal of the exposure leading to improved SAH. No significant relationship was found associating adverse (improved) health at t-1 with increased (decreased) rate of D&M in occupants´ dwellings at time t, adding support to the hypothesis of a causal relationship from D&M to health. These findings support and further reinforce the literature on the association of ...